Pharmacokinetics of Memantine after a Single and Multiple Dose of Oral and Patch Administration in Rats. Issue 2 (28th September 2015) - Lee, Soo‐Han; Kim, Seung‐Hyun; Noh, Yook‐Hwan; Choi, Byung‐Moon; Noh, Gyu‐Jeong; Park, Woo‐Dae; Kim, Eun‐Jung; Cho, Ik‐Hyun; Bae, Chun‐Sik
Abstract: Memantine is a non‐competitive N ‐methyl‐D‐aspartate (NMDA) receptor antagonist used to treat Alzheimer's disease. We investigated memantine pharmacokinetics after oral, IV and patch administration in rats, and compared memantine pharmacokinetics after multiple‐ or single‐dose oral and transdermal administration. Venous blood was collected at preset intervals in single‐ and multiple‐dose studies. Non‐compartmental pharmacokinetics was analysed for all formulations. The oral, IV and patch memantine doses were 10 mg/kg, 2 mg/kg and 8.21 ± 0.89 mg/kg, respectively. The maximum plasma concentration was lower and the half‐life longer after patch administration than oral and IV administration. Memantine bioavailability was 41 and 63% for oral and patch administration, respectively. Steady state was achieved around 24 hr for oral and patch administration. The mean AUC increased after oral or patch administration from single to multiple dose. The memantine patch formulation displayed a longer duration of action and lower peak plasma concentration. However, drug exposure was similar to the oral formulation at each dose. Additionally, the memantine patch formulation displayed a smaller interindividual variability and lower accumulation than the oral formulation.